The Ultrasmall Biocompatible CuS@BSA Nanoparticle and Its Photothermal Effects - Wan, Xiaofang; Liu, Maixian; Ma, Mingze; Chen, Danyang; Wu, Na; Li, Li; Li, Zhongjun; Lin, Guimiao; Wang, Xiaomei; Xu, Gaixia (Frontiers in Pharmacology, 2019)
Nanomaterials with localized surface plasmon resonance (LSPR) have exquisite optical properties, which allows a wide range of applications. Non-stoichiometric copper sulfides with active LSPR have drawn great attention, because its LSPR peak falls in NIR region that is suitable for deep bioimaging and photothermal therapy. Despite numerous biomedical applications, the biocompatibility and toxicity of copper sulfides have not been studied systematically. In this contribution, we synthesized the ultrasmall biocompatible copper sulfide nanoparticle encapsulated within bovine serum albumin (BSA), CuS@BSA. The physical feature of CuS@BSA were characterized. The MTT and flow cytometry assays were performed. The in vitro photothermal therapy was also investigated. The results indicated that such CuS@BSA nanoparticle was with an average TEM size of 8 nm, and an average DLS size of 15 nm. The lower concentration of CuS@BSA have no toxic for HeLa cells, but the critical apoptotic events occurred in HeLa cells after co-incubation with 45 µg/mL CuS@BSA for 48 h. The photothermal effect of the CuS@BSA in aqueous medium were concentration-dependent and time-dependent, which were also verified by flow cytometry and microscopy while the CuS@BSA were co-cultured with HeLa cells and treated with laser. This work designed an ultrasmall potential biocompatible nanoparticle, CuS@BSA, for cancer photothermal therapy, and provided the toxic information to guide safely its biomedical applications.